The dispute between Newton and Leibniz: Calculus (2024)
Professor Miguel Mendez offers a brief historical review of the dispute between Newton and Leibniz over authorship and priority in the creation of the Calculus. The controversy began in 1711 when John Keill, a follower of Newton, accused Leibniz of plagiarism in an article. Leibniz responded, claiming that he was unaware of Newton's method of fluxions when he wrote his papers. The Royal Society appointed a committee that issued a verdict in favor of Newton, without giving Leibniz an opportunity to defend himself. The dispute was continued in pamphlets and correspondence, even after Leibniz's death.